A comprehensive review of the physicochemical, quality and nutritional properties of Nigella sativa oil. Issue 4 (19th May 2019) - Mazaheri, Yeganeh; Torbati, Mohammadali; Azadmard-Damirchi, Sodeif; Savage, Geoffrey P.
ABSTRACT: Nigella sativa L . is an annual herb of the Ranunculaceae family, with the seeds called black cumin seed or black seed containing 34–39% oil. Its oil has many uses in traditional medicine and food industry. Black seed oil is a significant source of essential fatty acids, tocopherols (91–246 ppm), phytosterols (1993−2182 ppm), polyphenols (245–309 ppm), essential oils and other bioactive compounds. Thymoquinone is one of the important active compounds in the essential oil part of black seed oil with many health beneficial properties. Black seed oil is getting much attention either used alone or in combination with other vegetable oils. Therefore, providing information about the black seeds originating in different parts of the world, their oil composition and the effect of different oil extraction methods can be of great value. Environmental condition, cultivated areas, maturity period and storage conditions have significant effects on its properties. Black seed oil deserves more attention as a potential multi-purpose product. This article reviews the physicochemical properties, quality, and medicinal and nutritional aspects of black seed oil.